0563 UPPER AIRWAY STIMULATION FOR OBSTRUCTIVE SLEEP APNEA: OBJECTIVE AND PATIENT REPORTED OUTCOMES AFTER FIVE YEARS OF FOLLOW-UP. (28th April 2017) - Strollo, PJ; Soose, R; Badr, M; Strohl, KP
Abstract: Introduction: Upper airway stimulation has been shown to be safe and effective in participants with moderate-to-severe OSA in a large cohort study (STAR Trial) after one year and three years of follow-up. In this report, we aimed to assess the objective and patient reported outcomes after five-years of follow-up. Methods: A total of 126 participants received an implanted upper airway stimulation system (Inspire Medical Systems, Minnesota, USA) in a prospective phase III trial. The co-primary outcomes were Apnea Hypopnea Index (AHI) and 4% Oxygen Desaturation Index (ODI). The secondary outcome measures included the following patient reported outcomes: Epworth Sleepiness Scale (ESS) and the Functional Outcomes of Sleep Questionnaire (FOSQ). The results are presented as mean ± standard deviation unless otherwise specified. Results: As of December 15, 2016, a total of 52 of the 126 implanted participants have completed the on-going five-year follow up. The BMI remained unchanged from baseline of 28.4 ± 2.6 to 28.2 ± 2.3 at five years. The AHI was reduced from 30.6 ± 8.1 to 14.0 ± 18.4 (p<0.001) with median AHI reduced from 30.2 to 7.5 from baseline to five-year. The ODI was reduced from 28.9 ± 12.0 to 11.0 ± 17.1 (p<0.001) with median ODI from 25.4 to 4.9. The ESS was reduced from 11.6 ± 5.0 to 6.6 ± 4.5 (p < 0.001) and FOSQ was increased from 14.3 ± 3.2 to 17.6 ± 3.1 (p < 0.001). The patient reported nightly use at five years was 82% for the cohort. Conclusion: Upper airway stimulation maintained a sustained benefit on OSA severity (AHI and ODI) and patient report outcome measures (ESS and FOSQ) after five years of follow-up. Support (If Any): Inspire Medical Systems.